Model Pembelajaran PAI Berbasis Inklusivitas: Strategi Pembentukan Identitas Keagamaan Anak Generasi Alfa - Dela Zalia; Lina Indriani; Gusmaneli (Indo Publishing, 2026)
This study analyzes the urgent need for reconstructing Islamic Religious Education (PAI) design as a proactive strategy to build Inclusive Religious Identity in Generation Alpha amid the threat of digital polarization. As true digital natives, Generation Alpha is highly vulnerable to algorithmic echo chambers, risking the solidification of exclusive religious views. Therefore, Inclusivity in PAI must be elevated to function as a spiritual immunity rooted in the Islamic value trilogy of Tasamuh, Tawassuth, and Ta’awun to instill the teachings of rahmatan lil alamin. Employing a Qualitative approach through Literature Study, this research identifies a significant pedagogical deficit in traditional PAI methods (dominated by lecturing and rote memorization). To bridge this gap, PAI design must be fully adapted based on three core principles: Active and Contextual Learning, strengthening the Affective Focus, and Safe Digital Technology Integration. These principles are synthesized into the structured Inclusive PAI Implementation Model. This model encompasses three interactive domains Pedagogical, Ecological/Cultural, and Policy to provide a concrete operational roadmap for PAI practitioners in cultivating moderate and tolerant religious character in the digital age.